Documenting Horror: The Use of Sound in Non-Fiction 9/11 Films (Altre Modernità, 2011)
While conventional 9/11 documentaries focus on the most known and visible images of the attack, three films that work against this tendency, 9/11 (2002), 11'09''01 - September 11 (2002) and Fahrenheit 9/11 (2004), avoid the television news coverage of the towers and portray the attacks primarily through sound.These films avoid or scantly interject the too familiar footage, working instead with the audio track’s ability to convey the horrors of the event.  By emphasizing sound, these films address a challenge familiar to documentary studies: how to appropriately represent a historical event whose tragic scale makes aesthetic representation questionable.